Police Legitimacy and the Norm to Cooperate: Using a Mixed Effects Location-Scale Model to Estimate the Strength of Social Norms at a Small Spatial Scale - Jackson, Jonathan (Journal of quantitative criminology, 2021)
Test whether cooperation with the police can be modelled as a place-based norm that varies in strength from one neighborhood to the next. Estimate whether perceived police legitimacy predicts an individual’s willingness to cooperate in weak-norm neighborhoods, but not in strong-norm neighborhoods where most people are either willing or unwilling to cooperate, irrespective of their perceptions of police legitimacy.